The effect of calorie restriction on the anthropometric parameters, HOMA-IR index, and lipid profile of female office workers with overweight and obesity: a preliminary study - Sadowska-Krępa, Ewa; Gdańska, Agnieszka; Přidalová, Miroslava; Rozpara, Michał; Grabara, Małgorzata (International journal of occupational medicine and environmental health, 2022)
OBJECTIVES: This study evaluates the effect of a 3-month calorie restriction (CR) without snacking on the anthropometric parameters, Homeostatic Model Assesment of Insulin Resistance (HOMA-IR), and lipid profiles of female office workers with overweight or obesity, whose physical activity was limited during the COVID-19 pandemic lockdown. MATERIAL AND METHODS: Forty-eight women aged 20-38 years (28.9±5.24) with low physical activity levels were divided into a non-snacking (NS) group (N = 21) and a snacking (S) group (N = 27) prior to the dietary intervention. Their daily energy intake during the intervention was lowered by 30% compared with the baseline level, and the proportion of polyunsaturated fatty acids and fiber in their diet was increased (to >30 g/day). The proportion of saturated fatty acids and simple carbohydrates was also reduced. The study participants were assessed at the baseline and post-intervention for anthropometric variables (body weight, body fat percentage BMI, waist circumference, hip circumference, waist-to-hip ratio) and the concentrations of insulin, total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C). Moreover, the values for HOMA-IR, the atherogenic index of plasma (AIP), and the ratios of TC/HDL-C, TG/HDL-C, and LDL-C/HDL-C were calculated. RESULTS: All anthropometric parameter values obtained post-intervention were lower than the baseline in both groups. The serum insulin concentration and HOMA-IR decreased respectively by an average of 6% and 25% in the NS group and 37% and 45% in the S group. The lipid profiles of all participants improved significantly, with the LDL-C concentration showing a more promising trend in the S group (decrease by 27%) than in the NS group (17%). CONCLUSIONS: The study showed that CR improved the anthropometric parameters, HOMA-IR index, and lipid profiles of all participants. Int J Occup Med Environ Health. 2022;35(6):693-706.
Keywords: Humans; inzulin; Overweight; Caloric Restriction; lidé; Body Mass Index; Obesity; COVID-19; Insulin; Triglycerides; triglyceridy; nadváha; Cholesterol, LDL; Cholesterol, HDL; Female; Communicable Disease Control; kalorická restrikce; LDL-cholesterol; kontrola infekčních nemocí; pandemie; Pandemics; inzulinová rezistence; HDL-cholesterol; index tělesné hmotnosti; ženské pohlaví; obezita; Insulin Resistance